Fi Makrifat Al Jawahir Karya Reyhan Al Biruni: Kitab Rujukan Teknologi Manufaktur Logam Dunia: Fi Ma'rifat Al Jawahir by Raihan Al Biruni: Reference Book of World Metal Manufacturing Technology - Pramono, Agus (Nur Science Institute, 2022)
The Muslim scientist who became the scientific reference on the manufacturing sector was Reyhan al-Biruni. The processing of wrought iron and the manufacture of steel from cast iron is carried out through the carbonization process. The element carbon has a very significant influence on the strength of the metal. The maximum solubility of Fe3C in iron is: 6.67%. This is a series of calculations of the composition of the atomic weight of each constituent element, which is the atomic weight of Fe = 56, the atomic weight of Carbon 12. Calculation of steel compounds Fe3C = 56 X 3 = 180. The solubility of Carbon in steel is 6.67, coming from 2/180 X 100% = 6.67%. Metal processing that has received worldwide attention today is the ECAP method, which is capable of producing significant mechanical strength. The stages of the ECAP process start from the process of applying a compressive force to the sample that is placed in the mold. A special characteristic of ECAP is the ability to introduce fine grain refinement into large bulk samples. Capable of reducing the size of fine grains to the size of nanometers, resulting in a material that is able to provide maximum physical and mechanical properties. ECAP combines compressive stress and tensile stress in the mold. The ECAP formula was previously found in the book of Fi Makrifat Al Jawahir by Reyhan Al Biruni. The book it was explaine in great detail that when metal is bent there will be an increase in its strength because of the reaction between metals